2013
DOI: 10.1016/j.mjafi.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Infection control practices in health care: Teaching and learning requirements of medical undergraduates

Abstract: a b s t r a c tBackground: Compliance and implementation of infection control guidelines have been recognized as efficient means to prevent and control hospital acquired infections. Objectives: To evaluate knowledge and practices about infection control guidelines amongst medical students and to explore their education needs as perceived by them and faculty. Methods: A total of 160 final year students and 100 faculty members of one of the top medical colleges in India were selected by simple random sampling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…Throughout history, multiple investigations have been carried out in students and health workers to determine the degree of knowledge that they have about HAIs, as well as their attitude regarding the implementation of measures to prevent them, and the proper implementation of those measures when they have direct contact with patients. The results of those studies are divergent: some have reported insufficient knowledge of HAIs and their prevention, 8,9,[11][12][13] while others report adequate knowledge with specific deficiencies, 7,10,14,16,17 which coincides with the findings of the present study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Throughout history, multiple investigations have been carried out in students and health workers to determine the degree of knowledge that they have about HAIs, as well as their attitude regarding the implementation of measures to prevent them, and the proper implementation of those measures when they have direct contact with patients. The results of those studies are divergent: some have reported insufficient knowledge of HAIs and their prevention, 8,9,[11][12][13] while others report adequate knowledge with specific deficiencies, 7,10,14,16,17 which coincides with the findings of the present study.…”
Section: Discussionsupporting
confidence: 72%
“…In the present research, most of the respondents stated that they acquired knowledge about HAIs while they were studying in the university, which coincides with the reports of other researchers. 4,7,11,14,15 However, self-learning was also reported as an important source of knowledge. 4,11,13 This is a relevant finding, as some authors argue that undergraduate education in developing countries does not often emphasize the potential risk of the spread of communicable infections from either the environment or from other patients or staff, and the corresponding preventive measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, undergraduate nursing program should include intended learning outcomes relevant to IPC which needs to be met and achieved by the nursing students. [14,15] Although IPC competency among nursing students and graduates is considered a significant and ongoing global issue, only few studies consider this area. Thus, the teaching and practice requirements of undergraduate nursing students regarding these issues need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that one out of every 20 hospitalized patients will contract an HCAI. The risk is substantial not only for patients, but also for health care workers (HCWs), including medical students 79. Hence, it is essential for medical students to have adequate knowledge about infection prevention and control (IPC) practices and to incorporate these in the professional training of medical students.…”
Section: Introductionmentioning
confidence: 99%